METAFORA DALAM KITAB AMSAL DI ALKITAB (SEBUAH ANALISIS SEMANTIK) - KALENGKONGAN, MELISA ENGDYANE (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2017)
ABSTRACT This study is an attempt to identify, classify, and analyze the metaphor in the Book of Proverbs. Metaphor is a figurative language that takes two different things which not have relation. The purpose of this research is to get the form of metaphor and the meaning of metaphor in through sentences that had about metaphor. This research uses a descriptive method. There are three steps to finish this research. First step is preparation, the writer reads the Book of Proverbs to find out the data. The second step is data collection, the writer collects the metaphor found the proverbs then identifies the kinds of metaphor according to the theory of Lakoff and Johnson (2003). The third step is data analysis, to the data analyze about the metaphor in the Book of Proverbs in the Bible, the writer uses the theory from Lakoff and Johnson, to analyze and describe metaphor in the Book of Proverbs. The result of this research shows there are 27 metaphors in the Book of Proverbs in the Bible. There are divide into three kind metaphor According to the theory of Lakoff and Johnson (2003) thus are three form metaphor: anthropomorphic metaphor, animal metaphor, synesthetic metaphor found in the Book of Proverbs. The finding of this research support the theory of Lakoff and Johnson (2003). Keywords : Metaphor, Semantic analyze, Proverbs